Dorsolateral Prefrontal Cortex Volumes Remained Unchanged in Obsessive Compulsive Disorder - Ozdemir, Huseyin; Atmaca, Murad; Yildirim, Hanefi; Gurok, M. Gurkan (Kure Iletisim Grubu A S, 2013)
Background:The dorsolateral prefrontal cortex (DLPFC) is an important prefrontal section of cortex, associated with executive functions, attention, nonverbal memory, and visuospatial skills, which have been reported to be disabled in OCD. In addition, neurochemical alterations of the DLPFC have been reported in OCD. Methods: This magnetic resonance imaging (MRI) study used manual tracing to measure DLPFC volumes in OCD patients arelative to healthy controls. Results: The mean DLPFC volumes of the patients with OCD were not statistically different compared to those of healthy control subjects. Conclusion: Based on our finding that DLPFC volumes remained unchanged in patients with OCD, despite some limitating factors, the present study suggests that there may not be an underlying structural basis for neurochemical changes of the DLPFC as well as executive function disorders in OCD.
Obsesif kompulsif bozuklukta dorsolateral prefrontal korteks hacmi de?işmemiştir
Keywords: Prefrontal cortex; obsessive-compulsive disorder; magnetic resonance imaging; volume